Peran Guru Dalam Bimbingan Belajar Terhadap Minat Belajar Anak Usia Dini - Sari, Yulia Novita; Ahsan, Sukria (IAIN Ternate, 2023)
Learning interest is very essential for students in implementing the learning process at school, as well as students in early childhood. This study aims to determine the role of teachers in implementing tutoring to increase early childhood learning interest. The teaching and learning process requires students who have a sense of interest, attention and love for the lessons delivered by the teacher. Sometimes students do not have interest in the learning process. This research is descriptive qualitative research, the methods used for data collection are interviews, documentation and observation. The results of this study shows that there are students at the early childhood education level who have a low request to learn. In the learning process, there are students seem getting bored, do not pay attention to the teacher's explanation in class, having less participation and activeness in teaching and learning process. In this case, teacher play very important role to carry out tutoring to increase students' interest in learning.